Handgrip strength in elderly: an integrative review - Zanin, Caroline (2018)
Aims: The aim this study is was to review in the literature studies on the handgrip strength analysis in the elderly. Source of data: Were selected manually manuscripts in the Portuguese and English languages indexed in the electronic databases SciELO, Lilacs and MEDLINE starting from the primary descriptor “Força da mão” (“Hand Strength”) in crossroads with the secondary descriptors “Idoso” (“Aged”) and “Envelhecimento” (“Aging”), all according to the Descriptors of Health Sciences. Summary of findings: We included studies, with samples composed of elderly submitted to the hand strength test, by means of manual dynamometry. Was found 4155 articles in the search. Of these, 65 articles were read carefully and 08 were included in the present review. Conclusions: In short, older men have a higher palmar grip strength compared to women. Furthermore, risk factors such as osteoporosis, pain and malnutrition may influence in handgrip strength and general muscular strength of the elderly, and regular physical exercises may increase or prevent loss of manual force.